2019
DOI: 10.1186/s12883-019-1291-9
|View full text |Cite
|
Sign up to set email alerts
|

Stent-retriever assisted vacuum-locked extraction (SAVE) versus a direct aspiration first pass technique (ADAPT) for acute stroke: data from the real-world

Abstract: Background Embolectomy is the standard of care in acute ischemic stroke (AIS) caused by large vessel occlusion (LVO). Aim of this study was to compare two techniques: A Direct Aspiration First Pass Technique (ADAPT) and Stent-retriever Assisted Vacuum-locked Extraction (SAVE) stratified by the occluded vessel. Methods One hundred seventy-one patients (71 male) treated between January 2014 and September 2017 with AIS due to LVO of the anterior circulation (55 carotid T, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
33
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 35 publications
5
33
1
1
Order By: Relevance
“…The shift in clinical outcomes is best visualized in Figure 1 . These results are in accordance with those reported in other papers [ 5 , 6 , 13 , 18 , 19 , 22 , 23 , 28 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The shift in clinical outcomes is best visualized in Figure 1 . These results are in accordance with those reported in other papers [ 5 , 6 , 13 , 18 , 19 , 22 , 23 , 28 ].…”
Section: Discussionsupporting
confidence: 94%
“…Previous studies have shown that different techniques combining stent retrievers with aspiration catheters, such as SAVE, Solumbra or ARTS, present with high rates of reperfusion success and good clinical outcomes [ 5 , 6 , 13 , 14 , 15 , 16 , 17 ]. In 2019, Brehm et al, in a direct comparison, proved the superiority of SAVE over ADAPT in achieving faster and better recanalization with fewer device passes [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…After stratification according to the occlusion site, the combined approach was more efficient for carotid "T" occlusions with higher rates of recanalization (TICI 2c or more 55.2% vs 15.4%; p=0.025), with higher rates of first-pass mTICI 2c or more (59.6% vs 33.3%; p=0.019), and demonstrated a trend toward better final successful reperfusion rate (93.1% vs 65.4%; p=0.10). 59 For M1 segment occlusion, similar reperfusion rates were reported (94.8% vs 83.3%; p=0.187). Finally, two observational studies have also reported a lower rate of ENT with combined treatment but also an increased risk of sICH, 20 60 a difference that was not found in the RCT.…”
Section: Direct Aspiration Versus Combined Approachsupporting
confidence: 70%
“…According to this recent meta-analysis, 61 combined treatment was associated with better successful reperfusion rates (OR 1.47, 95% CI 1.02 to 2.12) compared with DA alone; however, there was no difference in clinical outcomes (favorable outcome OR 0.84, 95% CI 0.38 to 1.86). One study 59 further investigated this result. After stratification according to the occlusion site, the combined approach was more efficient for carotid "T" occlusions with higher rates of recanalization (TICI 2c or more 55.2% vs 15.4%; p=0.025), with higher rates of first-pass mTICI 2c or more (59.6% vs 33.3%; p=0.019), and demonstrated a trend toward better final successful reperfusion rate (93.1% vs 65.4%; p=0.10).…”
Section: Direct Aspiration Versus Combined Approachmentioning
confidence: 93%
“…Furthermore, no differences were found in reperfusion success between patients treated exclusively with stent-retrievers or those treated with aspiration devices, as has also been reported by the COMPASS trial [ 26 ], as well as by a recent meta-analysis [ 23 ]. In this context, it is of importance to note that recent studies have demonstrated that a combined approach, such as stent retriever-assisted vacuum-locked extraction (SAVE) appears to be superior in achieving reperfusion with a single pass [ 36 ].…”
Section: Discussionmentioning
confidence: 99%